Przyczyny wykluczenia osób starszych z rynku pracy w Polsce - Niewiadomska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In the last decade there has been a positive trend in the increase in occupational activity of the people from the older groups of the working population, but at the same time there emerges the worrying phenomenon of long-term unemployment in this group. The considerations contained in this study refer to older people, represented by those who belong to the older working age groups. Such a choice was dictated by their increasing share in the workforce and in the long-term unemployed group. The purpose of this article is to answer the question concerning the reasons and mechanism of exclusion of the elderly from the labor market. The point of departure of the discussion is an attempt to approximate the notion of exclusion from the labor market, then the analysis of long-term unemployment among unemployed people over 50 years of age. The main part of the article covers the analysis of factors that can be considered as determining the occupational exclusion of older people. The analysis used the results of research conducted among the unemployed over 50 in Poland as well as data of the Central Statistical Offi ce and the Local Data Bank
Keywords: labor market; older people; discrimination; exclusion; occupational activity